2015
DOI: 10.1080/09515070.2015.1023698
|View full text |Cite
|
Sign up to set email alerts
|

Client concealment and disclosure of secrets in outpatient psychotherapy

Abstract: This study investigated client motivations for concealing versus disclosing secrets in therapy as well as how this negotiation process relates to therapeutic process and outcome. About half of the participants had both revealed a secret and were concealing a secret in therapy. Disclosed secrets were most likely to be related to relationships and were disclosed because the clients felt they could trust their therapists and because they thought they could benefit from sharing the secret. Concealed secrets were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 69 publications
5
24
2
Order By: Relevance
“…In addition, 15% of participants never reported concealing or disclosing a secret, a finding similar to the 9% in Baumann and Hill (2015). These results suggest that a small percentage of clients are open and willing to talk about difficult experiences and thoughts with their therapists.…”
Section: Frequency Of Disclosure and Concealmentsupporting
confidence: 57%
See 1 more Smart Citation
“…In addition, 15% of participants never reported concealing or disclosing a secret, a finding similar to the 9% in Baumann and Hill (2015). These results suggest that a small percentage of clients are open and willing to talk about difficult experiences and thoughts with their therapists.…”
Section: Frequency Of Disclosure and Concealmentsupporting
confidence: 57%
“…Psychotherapy would seem to provide hospitable conditions for disclosing secrets, given that there is generally a trustworthy relationship, a safe environment, and a confidante who is contractually bound to maintain confidentiality and is likely to respond in a positive and therapeutic manner (Greene, Magsamen-Conrad, Venetis, Checton, Bagdasarov, & Banerjee, 2012; Omarzu, 2000). Yet, 28% to 53% of clients in psychotherapy admit to concealing a secret from their therapist (Baumann & Hill, 2015; Hill, Thompson, Cogar, & Denman, 1993; Kelly, 1998; Kelly & Yuan, 2009). Furthermore, Baumann and Hill (2015) found that immediately following the disclosure of a secret, clients experienced similar levels of both positive and negative emotions, indicating that disclosure may have costs as well as benefits.…”
mentioning
confidence: 99%
“…As concealment of cultural identities has only been measured within the context of broader measures, this study represents the first use of a cultural concealment scale in the psycho-therapy literature. Items for this scale were generated after a careful review of the existing concealment and disclosure literature and the phrasing of items used within it (e.g., Baumann & Hill, 2016). We examined the content validity of these items via three psychologists with expertise in multicultural competencies and psychotherapy research.…”
Section: Methodsmentioning
confidence: 99%
“…The therapeutic process in psychotherapy is aimed at facilitating clients' capacity to approach, recognize and reflect upon challenging life issues with openness and authenticity (Kolden et al, 2018). However, the process of opening up in treatment sessions is far from straightforward, as apprehension, shame or fright can prevail (e.g., MacFarlane et al, 2015;Baumann and Hill, 2016;Marks et al, 2019). It is natural that disclosure of personal material can take some time, sometimes opening up may occur only after months and sometimes it never happens (Farber, 2003).…”
Section: Introductionmentioning
confidence: 99%